Pengaruh Rasio Keuangan terhadap Harga Saham Rumah Sakit Privat yang Terdaftar di Bursa Efek Indonesia - Nurjanah, Risandy Meda (Owner : Riset dan Jurnal Akuntansi, 2024)
Private Hospital is a health institution aimed at profit. Some of them even trade shares on the stock exchange to obtain additional capital. The literature that examines share price of hospitals is still limited. For this reason, this research aims to obtain empirical results regarding the effect of financial ratios on private hospital stock prices. This research was conducted in Indonesia with testing year 2016 to 2022. Data source was obtained from OSIRIS with SIC 806. Researchers used STATA14 to carry out statistical tests. The tests carried out are Pearson correlation test, Classical assumption test, and Multiple linear regression test. Results show that ROA has a positive effect on stock prices, but other financial ratios used in the model have no significant effect.